2018
DOI: 10.1161/circulationaha.117.032235
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol Lowering With Evolocumab and Outcomes in Patients With Peripheral Artery Disease

Abstract: BACKGROUND:The PCSK9 (proprotein convertase subtilisin/kexin type 9) inhibitor evolocumab reduced low-density lipoprotein cholesterol and cardiovascular events in the FOURIER trial (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk). We investigated the efficacy and safety of evolocumab in patients with peripheral artery disease (PAD) as well as the effect on major adverse limb events. METHODS:FOURIER was a randomized trial of evolocumab versus placebo in 27 564 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(107 citation statements)
references
References 39 publications
(53 reference statements)
3
100
0
4
Order By: Relevance
“…Similarly, in the FOURIER Trial, PCSK9 inhibition with evolocumab significantly reduced LDL cholesterol level and reduced the risk of major adverse limb events in patients with peripheral artery disease. Future studies should be planned to evaluate its effect on outcome in kidney CKD patient [50]. A recent review published by Zeng Lin et al [51] also examined the 2 novel studies focusing the efficiency of PCSK9 inhibitors.…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 Effect On Lipimentioning
confidence: 99%
“…Similarly, in the FOURIER Trial, PCSK9 inhibition with evolocumab significantly reduced LDL cholesterol level and reduced the risk of major adverse limb events in patients with peripheral artery disease. Future studies should be planned to evaluate its effect on outcome in kidney CKD patient [50]. A recent review published by Zeng Lin et al [51] also examined the 2 novel studies focusing the efficiency of PCSK9 inhibitors.…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 Effect On Lipimentioning
confidence: 99%
“…The full study which was placebo controlled, of evolocumab, showed a significant decrease in the combined CV endpoints of MI, Stroke, and death (HR 0.80, 95 % CI 0.73-0.88) combined with a very good safety profile for very low levels of LDL. In the PAD subgroup, evolocumab significantly reduced the primary end point consistently in patients with PAD (hazard ratio [HR] 0.79; 95 % confidence interval [CI], 0.66-0.94, and also reduced the risk of major adverse limb events in all patients (HR, 0.58; 95 % CI, 0.38-0.88) [133]. This suggests that current targets are set to fall as these new drugs reach endpoint study conclusion.…”
Section: Amentioning
confidence: 99%
“…Intriguingly, there is also some evidence in support of lipid lowering improving claudication. In the Scandinavian Simvastatin Survival Study (4S), simvastatin served to reduce the development of intermittent claudication in patients with coronary and stroke disease [128][129][130][131][132][133][134]. Further studies applying various doses of atorvastatin or simvastatin to treat patients with claudication yielded significantly improved pain-free or absolute walking distances compared to placebo after 3, 6, and 12 months.…”
Section: Amentioning
confidence: 99%
“…Thus, even considering the lack of significant adverse events in patients treated with evolocumab and the evidence that 42% of evolocumab treated patients achieved LDL-C levels\25 mg/dl without manifesting relevant side effects, including no change in cognitive function [11], benefits from the evolocumab-induced marked LDL-C reductions appeared to be not lower than expected. In keeping to this, a NNT = 29 over 2.5 years have been recently indicated in FOURIER patient's with peripheral artery disease at baseline [12].…”
mentioning
confidence: 90%